Cardiovascular magnetic resonance with parametric mapping in long-term ultra-marathon runners. Issue 117 (August 2019) - Małek, Łukasz A.; Barczuk-Falęcka, Marzena; Werys, Konrad; Czajkowska, Anna; Mróz, Anna; Witek, Katarzyna; Burrage, Matthew; Bakalarski, Wawrzyniec; Nowicki, Dariusz; Roik, Danuta; Brzewski, Michał
Highlights: Ultra-marathon runner's hearts demonstrate high degree of structural remodelling. In majority of them heart chamber size exceeds normal reference values. Myocardial wall thickness does not change significantly. There is no significant increase in focal or diffuse myocardial fibrosis. Abstract: Purpose: There is a direct reverse dose-effect relationship between the amount of physical activity and cardiovascular risk. It is unknown whether this is true for extreme, persistent endurance training. The aim of the study was to assess structural changes of the heart in long-time ultra-marathon runners with special focus on myocardial fibrosis using parametric mapping. Method: We studied a group of 30 healthy, male ultra-marathon runners (mean age 40.9 ± 6.6 yrs, median 9 yrs of running with frequent competitions) and 10 matched controls not engaged in any regular activities. All of them underwent cardiovascular magnetic resonance (CMR) with 3 T scanner including T1-mapping, late gadolinium enhancement (LGE) and extracellular volume (ECV) quantification. Results: Athletes demonstrated significantly larger heart chambers and left ventricular (LV) mass. LV systolic function was unchanged. 73.3% of athletes fulfilled volumetric criteria for dilated cardiomyopathy or arrhythmogenic right ventricular cardiomyopathy. Non-ischemic, small volume LGE was found in 8 athletes and in 1 control (27% vs. 10%, p = 0.40). It was localised at insertion points (5 athletes, 1 control) or in the septum or infero-lateral wall (3 athletes). Athletes with insertion point LGE had higher right ventricular end-diastolic volume index in comparison to athletes without LGE (p = 0.04), which suggests its relation to volume overload. There were no differences between athletes and non-athletes in terms of ECV values (26.1% vs. 25%, p = 0.29). Conclusions: Ultra-marathon runner's hearts demonstrate a high degree of structural remodelling, but there is no significant increase in focal or diffuse myocardial fibrosis.